Hans J. Morgenthau papers - Morgenthau, Hans J. (Hans Joachim), 1904-1980.; Morgenthau, Hans J. (Hans Joachim), 1904-1980.
Correspondence, lectures, writings, academic files, subject files, printed matter, and other papers primarily relating to Morgenthau's career as an analyst of international relations from the World War II era until his death in 1980. Documents his work at the University of Chicago (1943-1971) and the New School for Social Research (1974-1980). Includes drafts and galley proofs of his books including Politics Among Nations (1948) and of his articles for Commentary, New Leader, New Republic, New York Review of Books, and New York Times. Also documents his association with the Academic Committee on Soviet Jewry, American Academy of Political and Social Science, Americans for Democratic Action, American Jewish Congress, Carnegie Endowment for International Peace, Council on Foreign Relations, and University of Chicago Center for the Study of American Foreign Policy (later Center for the Study of American Foreign and Military Policy). Subjects include Abraham Lincoln, U.S.-Soviet détente, and the Vietnam War.
Correspondents include Dean Acheson, Hannah Arendt, Raymond Aron, Waldemar Gurian, Robert Maynard Hutchins, Gustav Ichheiser, Henry M. Jackson, Hans Kelsen, Henry Kissinger, Alfred A. Knopf, Alfred M. Landon, Ernest W. Lefever, Walter Lippmann, Irma Thormann Morgenthau, Robert J. Myers, Reinhold Niebuhr, Paul H. Nitze, David Riesman, Dean Rusk, and Joseph J. Sisco.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Political scientist, educator, and author. Born in Germany, emigrated to the United States in 1937.
Collection material in English, with German and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Dean, -- 1893-1971 -- Correspondence; Arendt, Hannah, -- 1906-1975 -- Correspondence; Aron, Raymond, -- 1905-1983 -- Correspondence; Gurian, Waldemar, -- 1902-1954 -- Correspondence; Hutchins, Robert Maynard, -- 1899-1977 -- Correspondence; Ichheiser, Gustav -- Correspondence; Jackson, Henry M. -- 1912-1983 -- Correspondence; Kelsen, Hans, -- 1881-1973 -- Correspondence; Kissinger, Henry, -- 1923- -- Correspondence; Knopf, Alfred A., -- 1892-1984 -- Correspondence; Landon, Alfred M. -- 1887-1987 -- Correspondence; Lefever, Ernest W., -- 1919- -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lippmann, Walter, -- 1899-1974 -- Correspondence; Morgenthau, Irma Thormann -- Correspondence; Myers, Robert J. -- 1924- -- Correspondence; Niebuhr, Reinhold, -- 1892-1971 -- Correspondence; Nitze, Paul H. -- Correspondence; Riesman, David, -- 1909-2002 -- Correspondence; Rusk, Dean, -- 1909-1994 -- Correspondence; Sisco, Joseph J. -- Correspondence; Academic Committee on Soviet Jewry; American Academy of Political and Social Science; Americans for Democratic Action; American Jewish Congress; Carnegie Endowment for International Peace; Council on Foreign Relations; New School for Social Research (New York, N.Y. : 1919-1997); Rockefeller Foundation; University of Chicago -- Faculty; University of Chicago. -- Center for the Study of American Foreign and Military Policy; University of Chicago. -- Center for the Study of American Foreign Policy; Commentary (New York, N.Y.); New leader (New York, N.Y. : 1935); New republic (New York, N.Y.); New York review of books; New York times; Detente; International relations; Political science; Vietnam War, 1961-1975.; Russia -- Foreign relations -- United States; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Russia; United States -- Foreign relations -- Russia; Authors; Educators; Political scientists